Direct measurement of the mass difference of 163Ho and 163Dy solves the Q-value puzzle for the neutrino mass determination - Eliseev, Sergey; Enss, Christian; Gastaldo, Loredana (Physical review letters, 2015)
The atomic mass difference of 163Ho and 163Dy has been directly measured with the Penning-trap mass spectrometer SHIPTRAP applying the novel phase-imaging ion-cyclotron-resonance technique. Our measurement has solved the long-standing problem of large discrepancies in the Q value of the electron capture in 163Ho determined by different techniques. Our measured mass difference shifts the current Q value of 2555(16) eV evaluated in the Atomic Mass Evaluation 2012 [G. Audi et al., Chin. Phys. C 36, 1157 (2012)] by more than 7σ to 2833(30stat)(15sys) eV/c2. With the new mass difference it will be possible, e.g., to reach in the first phase of the ECHo experiment a statistical sensitivity to the neutrino mass below 10 eV, which will reduce its present upper limit by more than an order of magnitude.